أثر الأوبئة في تغيُّر الفتاوى الخاصة بالعبادات: وباء كوفيد-19 أنموذجًا: (The Impact of Infectious Diseases on Affecting the Original Fatwas on Worship: The Case of COVID-19 Pandemic) - Hassan Suleiman; Mahamed Fathy Eletrebi; Auwal Adam Sa'ad (At-Tajdid - Intellectual Refereed Journal, 2023)
Abstract The pupose of this study is to look at the effect of infectious disesases on Ibādah issues during the COVID- 19 pandemic. The paper looks into the available Shari’ah rules to be realized in the making of new fatwas issued specifically to help contain the pandemic crisis. The paper has deliberated on issues related to fatwah changes and their critical implications in Sharīʿah and also gives background on the need to change fatwas that originated from the Qur’ān and Sunnah and implement them in the new jurisprudential issues that occurred during the pandemic. The methodology adopted in this paper is a descriptive analysis, by understanding and identifying the related literature on the topic and analyzing them according to the classical fiqh opinions. The paper maintained that it is applicable in Shari’ah to change fatwas according to the change of time, places, and situations. This is mainly to either achieve a (clear societal benefit) or prevent a (clear societal harm) and maintain the possibility of effecting such new fatwas during the COVID-19 pandemic. Keywords: Fatwa changes; ibādāt; pandemic period, COVID-19.